Non-linear Relationship Between Body Mass Index and Lower Urinary Tract Symptoms in Korean Males - Chang Kyun Choi; Sun A Kim; Ji-An Jeong; Sun-Seog Kweon; Min-Ho Shin (Journal of Preventive Medicine and Public Health, 2019)
Objectives: The purpose of this study was to evaluate the association between body mass index (BMI) and severe lower urinary tract symptoms (LUTS) in Korean males. Methods: This study was conducted on males aged ≥50 years who participated in the 2011 Korean Community Health Survey. LUTS severity was assessed using the Korean version of the International Prostate Symptom Score (IPSS) questionnaire, and was dichotomized as severe (IPSS >19) and non-severe (IPSS ≤19). BMI was divided into 6 categories: <18.5, 18.5-22.9, 23.0-24.9, 25.0-27.4, 27.5-29.9, and ≥30.0 kg/m2. To evaluate the relationship between BMI and LUTS, a survey-weighted multivariate Poisson regression analysis was performed to estimate prevalence rate ratios (PRRs). Age, smoking status, alcohol intake, physical activity, educational level, household income, and comorbidities were adjusted for in the multivariate model. Results: A U-shaped relationship was detected between BMI and severe LUTS. Compared with a BMI of 23.0-24.9 kg/m2, the PRR for a BMI <18.5 kg/m2 was 1.65 (95% confidence interval [CI], 1.35 to 2.02), that for a BMI of 18.5-22.9 kg/m2 was 1.25 (95% CI, 1.09 to 1.44), that for a BMI of 25.0-27.4 kg/m2 was 1.20 (95% CI, 1.00 to 1.45), that for a BMI of 27.5-29.9 kg/m2 was 1.11 (95% CI, 0.83 to 1.47), and that for a BMI ≥30.0 kg/m2 was 1.85 (95% CI, 1.18 to 2.88). Conclusions: This study showed that both high and low BMI were associated with severe LUTS.